Surgical versus non-surgical management of orbital fractures: study protocol for evidence generation of a prospective multicentre observational cohort registry - Eppo B Wolvius; Elske M Strabbing; Florian Thieringer; Drago B Jelovac; Moustafa Al-Khalil; Vivesh Rughubar; Philippe Korn; Omri Emodi; Alvaro Rivero Calle; Sergey Epifanov; Wenko Smolka; Pasquale Piombino; et al. (BMJ Open, 2025)
Introduction There remains little consensus or guidelines for the clinical management of traumatic orbital fractures (OFx). The OFx Registry aims to increase real-world clinical evidence for the treatment of OFx via prospective, multicentre, international data collection. The primary objectives of this observational cohort study are (1) to document current treatment practices for and (2) to assess the outcomes of surgical and non-surgical treatment of orbital floor and/or medial wall fractures.Methods and analysis Approximately 300 adult patients presenting with a displaced OFx in the orbital floor and/or medial wall will be enrolled prospectively over a recruitment period of ~36 months. All eligible patients treated either surgically or non-surgically as per routine standard of care will have follow-up assessments at 6 weeks, 3 months and 6 months post-treatment. Demographic data, injury details, treatment details and outcome measures will be documented in a cloud-based database. Outcome measures include clinical outcomes (eg, diplopia, extraocular motility, and condition of the eyelid, globe and soft tissues), radiological outcomes from collected images, patient-reported outcomes (eg, Diplopia Questionnaire and the newly developed AO Craniomaxillofacial (CMF) Injury Symptom Battery) and complications. A statistical analysis plan will be prepared before final analysis summarising the descriptive statistics to be used for data assessment. Appropriate research questions and statistical tests may be applied additionally, depending on the availability and quality of data collected.Ethics and dissemination Ethics approval was obtained before patients were enrolled at each participating site. Patient enrolment followed an informed consent process approved by the responsible ethics committee. Peer-reviewed publications are planned to disseminate the study results.Trial registration number NCT03887988.